TINDAK PIDANA PERDAGANGAN ORANG DALAM PERSPEKTIF KRIMINOLOGI - Rini Retnowinarni (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
The rapid development of science and technology, has had an impact on the level of human civilization that brought about a major change in the form of community patterns and behavior. In this era of globalization, the crime of human trafficking which is a transnational crime or transnational crime has become a global concern of States in the world. Especially for Indonesia in order to ensnare the perpetrators of the criminal acts of trafficking of persons we use Law No. 21 of 2007 on the Eradication of Crime of Trafficking in Persons. The criminal acts of trafficking in persons seen in criminological perspectives can be attributed to a whole range of different matters, including the lack of awareness of poverty, low education, the desire for rich quickness, cultural factors, law enforcement. In the framework of national instruments, Indonesia in making countermeasures trafficking of persons through several ways to raise or cooperate with relevant agencies. also undertake the improvement and supervision of relevant agencies and take firm action against labor recruitment agencies especially those reinforced by government regulations and ministerial decisions to jointly address the issue of trafficking in persons